Design Of Portable Cold Storage Using Solar Power - Defri Pratama; Desmarita Leni; Dedi Erawadi; Hendri Candra Mayana (Universitas Negeri Padang, 2024)
This research aims to design and analyze a portable cold storage system that uses solar energy as the main power source. The research methods used include literature studies, system design, and design analysis to evaluate the performance of the cold storage being designed. The designed system has a volume of 2.93 liters with an operational temperature of -2°C, which requires a total energy requirement of 114,912 kWh per day to maintain storage temperature stability under external environmental conditions of 30°C. The solar panels used have an efficiency of 18% with a standard irradiation exposure of 1000 W/m², capable of producing 4,788 watts of power, which shows sufficient efficiency to meet the cold storage energy needs. Based on the analysis, it is estimated that 43.2 solar panels are needed to meet daily energy needs, which indicates the large scale of energy infrastructure needed to maintain cold storage operations 24 hours a day. In addition, to ensure operational continuity, especially at night or when exposure to sunlight is low, energy storage capacity in the form of batteries of 230 kWh is required so that the cold storage can function without interruption. The results of this research show that with proper planning, the use of renewable energy through solar power can be optimized to support the sustainability of cold storage operations, even in environments with significant energy availability challenges. This research makes an important contribution to the development of efficient and sustainable portable cold storage technology